DETERMINANTS OF THE UTILIZATION OF AGRO-PROCESSING, PRODUCTIVITY ENHANCEMENT AND LIVELIHOOD IMPROVEMENT SUPPORT PROJECT AMONG RICE FARMERS IN KANO STATE, NIGERIA - Iliyasu, S.; Dutse, F.; Kehinde, E. A. (Nigerian Journal of Agriculture and Agricultural Technology, 2025)
The study evaluates the determinants of the utilization of the Agro-Processing, Productivity Enhancement, and Livelihood Improvement Support (APPEALS) Project among rice farmers in Kano State, Nigeria. A multi stage sampling techniques was used in selecting 319 respondents. Data were collected using structured questionnaires and were analysed using descriptive and inferential statistics. The results revealed that the mean utilization percentage of the Project is 62.6% and more than (57.2%) of the respondents utilized 11 and above activities and are considered as high utilization category, factors influencing the utilization of the project include age (0.015) at 1 percent level of probability, sex (0.045) at 5 percent level of probability, household size (1.025) at 1 percent level of probability, extension contact (0.025) at 1 percent level of probability, and membership of cooperative (0.060) at 1 percent level of probability were all found to influence participation in the APPEALS Project at 1% and 5% levels of probability. It further shows that beneficiaries faced challenges such as high costs of production, ranked 1st, inconsistency in extension services delivery, ranked 2nd and market price fluctuations ranked 3rd. This study can be concluded that beneficiaries and non-beneficiaries were at their productive age, and the beneficiaries of the APPEALS Project tremendously utilized the components of the Project very well. The level of the utilization of the project components were influenced by some socio-economic and institutional factors and. However, the beneficiaries of the project were constrained by certain hindrance such as high cost of production inputs. The study recommends that reducing the price fluctuation, and extending the project benefits beyond its direct participants by fostering inclusiveness of non-beneficiaries from other communities will widen or strengthen the impact.